Gambaran Kepatuhan Masyarakat terhadap Protokol Keluar dan Masuk Rumah Pada Masa Pandemi Covid-19 di Kelurahan Mande Kota Bima - Aniharyati Aniharyati; A.Haris A.Haris; Hengky Lukas Wambrauw (Poltekkes Kemenkes Mataram, 2022)
Coronaviruses were a large family of viruses that cause disease in humans and animals. In humans, it usually causes respiratory tract infections, ranging from the common cold to serious illnesses such as Middle East Respiratory Syndrome (MERS) and Severe Acute Respiratory Syndrome (SARS). A new type of coronavirus found in humans since an extraordinary event appeared in Wuhan, China, in December 2019, was later named Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-COV2), and caused Coronavirus Disease-2019 (COVID-19). This research was a descriptive study to find out the description of community compliance with the protocol for leaving and entering the house during the covid-19 pandemic. This research was conducted in Mande Village, Bima City within 9 months. The population were all head of family in Mande subdistrict totaling 60 families who met the inclusion criteria. The results showed that the majority of respondents had a bachelor's level of education as many as people (71,7%). While the respondents who were the level of compliance when leaving the house were 42 people (70.3%) and when entering the home as many as 49 people (81.7%). The high level of non-compliance as many as 13 people (21.7%) was in the act of shopping using non-cash